SCIENTIFIC EVIDENCE FOR WALLS FASTENING TECHNOLOGIES OF WORKING TRENCH BY THE SPECIAL METHOD “SLURRY WALL” FOR SHALLOW SUBWAYS’ STATIONS - Borshchevskiy, S. V.; Petrenko, V. D.; Tiutkin, O. L.; Kulazhenko, Ye. Yu.; Kulazhenko, O. M. (Science and Transport Progress, 2014)
Purpose. It’s necessary to carry out justification of fastening technology and the choice of the optimal variant, creating dependency diagrams of moving for idealized cases by means of automated methods of calculations. Methodology. To achieve this goal, the finite element solid models, which reflect the design of the working trench for the shallow subways’ stations, with four ways to fix the “slurry wall”, as well as a calculation and analysis of the stress-strain state of structures and fixtures calculated using the complex with using the finite element method (FEM) is built in the software package SCAD. Findings. The analysis of the stress-strain state and movements of various fundamental systems of soil nailing and comparing the results by displaying the calculations results of main and equivalent stresses, using the built-in postprocessors in software package SCAD. Namely, were identified extreme tensions arising in the wall and strut rail. It is built the tables and the resulting graph of behavior of the structural fastening condition; the parameters change of the surrounding array on the base of the research. It is possible to analyze and compare the operation of different constructions of slopes fastening of working trench by means of their help. Originality. In solving this problem have been analyzed and studied the behavior of the structure fastening the «slurry wall», and its stress-strain state, the location and the fastening areas that need further elaboration, study and introduction of measures to strengthen the construction of fences and auxiliary fixing elements, presented with metal strut rail. Practical value. In the era of highly advanced building technologies in the construction of underground facilities with using the special method of “slurry wall” the question arises about the quick selection of optimal parameters, elements and methods of securing its walls from excessive strain and avoidance of displacement to the calculation of possible combinations of permanent loads from soil in the construction of the working trench.